PASSION, PIPELINES, AND PRECARITY: WORKING LIVES IN GAMES FROM THE PERSPECTIVE OF HIGHER EDUCATION - Harvey, Alison (AoIR Selected Papers of Internet Research, 2021)
For years, academics and journalists have proclaimed a crisis of gameswork, detailing the ‘destruction’ of the lives of those in this creative workforce, and wondering when the ‘breaking point’ of professional game design, premised on crunch, work limbo, and churn, would come. Still it was only at the March 2018 Game Developers Conference, typically a heavily corporatized event, that a large-scale discussion of unionization was staged, leading to the formation of Game Workers Unite. While collective organizing in games is going global, with branches forming from France to Australia to South Korea, these developments are outpaced by increasingly transnational dynamics of outsourcing and automation, threatening to devalue and even eliminate already highly-competitive jobs in ‘cool industries’ of ‘passionate’ workers. This paper considers these global contradictions and tensions through analysis of a group heavily implicated in visions of the future of gameswork- students in formal games education. While within game studies there has been sustained interest in the production of this form and labour relations therein, the shape and role of games higher education remains underexplored. The existing scholarship indicates that these formal sites of training tend to cultivate the still-largely young, male, and passionate fan-workforce on which games depend. Furthermore, these contexts are vital in the formation of future gamesworker identities that are conservative, uncritical, and risk-adverse, despite pervasive discourses of creativity and innovation linked to them. Vitally, however, the question of how these norms relate to shifting work realities has yet to be explored.